2006
DOI: 10.1021/jf0604541
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Known Antioxidants and of Press Juice from Herring (Clupea harengus) Light Muscle on the Generation of Free Radicals in Human Monocytes

Abstract: Reactive oxygen species (ROS) can cause oxidative stress, which has been linked to various diseases. It has been suggested that antioxidant-rich foods can reduce such oxidative stress. However, the lack of suitable model systems to screen for in vivo effects of food-derived antioxidants has prevented a clear consensus in this area. In this study, the aim was to use a single-cell model system (human monocyte) to evaluate whether certain pure antioxidants and complex muscle extracts (herring light muscle press j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…The LMPJ sample at the start of digestion had numerous bands ranging from 181 kDa to below 5 kDa size (Figure 4, lane 1). This was in accordance with Gunnarsson et al (6), who reported herring PJ to comprise many peptides distributed over a broad range of molecular size. The supernatant resulting from centrifugation of the 0 min digested LMPJ sample also had numerous bands (Figure 4, lane 2), showing that most of its proteins/peptides were soluble.…”
Section: Resultssupporting
confidence: 92%
“…The LMPJ sample at the start of digestion had numerous bands ranging from 181 kDa to below 5 kDa size (Figure 4, lane 1). This was in accordance with Gunnarsson et al (6), who reported herring PJ to comprise many peptides distributed over a broad range of molecular size. The supernatant resulting from centrifugation of the 0 min digested LMPJ sample also had numerous bands (Figure 4, lane 2), showing that most of its proteins/peptides were soluble.…”
Section: Resultssupporting
confidence: 92%
“…Intake of such antioxidants in a fish meal could theoretically help prevent oxidative stress in the body, caused by the easily oxidised n -3 PUFA. The liquid fraction (press juice) from herring was found to prevent oxidation in a food system ( 6 ) and to have antioxidative effects in a human monocyte model system ( 7 ) . Second, fish contains high concentrations of Se, which has been related to a reduced risk of CVD ( 8 , 9 ) .…”
mentioning
confidence: 99%
“…This table is reproduced from Gunnarson et al(19); however, additional statistical treatment is included.…”
mentioning
confidence: 99%